1978
DOI: 10.1007/bf00220400
|View full text |Cite
|
Sign up to set email alerts
|

Segmental and interganglionic projections from primary fibres of insect mechanoreceptors

Abstract: Projections of primary insect mechanoreceptor fibres in Locusta migratoria and Acheta domesticus are visualised with the cobalt intensification technique after axonal or dendritic filling with cobaltous chloride. Chordotonal proprioceptors of the locust mesothoracic thoracocoxal joint have typical segmental projections and more or less widespread interganglionic processes into the metathoracic, prothoracic and even suboesophageal ganglia. Similar observations can be made on locust abdominal chordotonal organs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 19 publications
1
40
0
2
Order By: Relevance
“…6h). The location, number of sensory neurons, and dendritic orientation of these pleural COs match those in locusts (Hustert 1978). The other group is located in the medio-ventral region of abdominal sternites (Fig.…”
Section: Abdominal Chordotonal Organs In Stink Bugsmentioning
confidence: 61%
See 1 more Smart Citation
“…6h). The location, number of sensory neurons, and dendritic orientation of these pleural COs match those in locusts (Hustert 1978). The other group is located in the medio-ventral region of abdominal sternites (Fig.…”
Section: Abdominal Chordotonal Organs In Stink Bugsmentioning
confidence: 61%
“…6f and S2a). There are two populations of COs. One group is located in the pleural fold between tergites and sternites of abdominal segments, designated pleural COs after Hustert (1978). Each pleural CO contains one sensory neuron (Fig.…”
Section: Abdominal Chordotonal Organs In Stink Bugsmentioning
confidence: 99%
“…The information then has to travel to the neighboring segment. Hardly any direct connections from sensory neurons into neighboring segments have so far been demonstrated (Hustert, 1978), but with connective lengths averaging about 17mm between the prothorax and mesothorax and 10mm between the mesothorax and metathorax (Cruse, 1976), and with conductance velocities within the connective of about 2-2.8mms -1 (Brunner et al, 1990), one can assume at least another 4-9ms until the first spikes reach the neighboring ganglion. Depending on how far distal in the leg the innervated muscle is, it takes an additional 1-5ms for the motoneuron spikes to travel to the neuromuscular end plate (Höltje and Hustert, 2003).…”
Section: Targeting Accuracy Changes Between Standing and Moving Targementioning
confidence: 98%
“…In locusts, it has been shown that signals from leg sense organs are largely conveyed by intersegmental interneurons to other ganglia and only rarely do sense organs have intersegmental projections (Hustert, 1978). The intersegmental interneurons can be descending (Laurent, 1987;Laurent and Burrows, 1989a;Laurent and Burrows, 1989b) or ascending (Laurent and Burrows, 1988).…”
Section: Gaits In Amputees and Inter-leg Controlmentioning
confidence: 99%